Registro e fusão semiautomática de imagens térmicas e anatômicas utilizando transformações não rígidas - Bueno, Alexandre Pereira (2016)
Thermal images, or infrared images, contain only functional information about the body, without anatomical information. The lack of an anatomical reference can compromise visual inspection. For this reason, functional medical images are combined with anatomical images, as in the case of the fusion of magnetic resonance or ultrasound anatomical images and PET functional images. Considering this, the present work presents a method for registration and fusion of thermal and anatomical images, with the purpose of providing anatomical references to thermal images and facilitate its analysis in diagnoses. Due to the morphological differences between the anatomical and functional images, it is necessary to transform at least one of them. For this purpose a method of non-rigid transformation with B-splines and manual landmarks was adopted. There are no reports of the application of this technique to thermal images and images from anatomical atlas, despite being used in other fields. Experiments were performed with thermal and anatomical images, the latter from atlas and visible light photographs, from different parts of the human body. The proposed method is capable of including information from anatomical images to thermal images through their registration and fusion, with errors in the order of 5 mm.